Oxonium trans‐bis(oxalato)rhodate and related sodium salts: a rare example of crystalline complex acid. Issue 6 (29th November 2021) - Garkul, Ilia; Zadesenets, Andrey; Filatov, Evgeny; Baidina, Iraida; Tkachev, Sergey; Samsonenko, Denis; Korenev, Sergey
Abstract : The polymorphism of Na[Rh(H2 O)2 (C2 O4 )2 ]·2H2 O is noteworthy. The complex crystallizes with the formation of two different structures of the same water content. Oxalato‐rhodic acid not only exists in solution, but, unlike most complex acids, it can also crystallize as a tetrahydrate. Abstract : New coordination compounds trans ‐bis(oxalato)diaquarhodiate sodium dihydrate Na[Rh(H2 O)2 Ox2 ]·2H2 O (crystallizes in two polymorphic forms NaRh‐1 and NaRh‐2), trans ‐bis(oxalato)hydroxoaquarhodiate sodium tetrahydrate Na2 [Rh(H2 O)(OH)Ox2 ]·4H2 O (Na2Rh) and trans ‐bis(oxalato)diaquarhodic acid tetrahydrate (H3 O)[Rh(H2 O)2 Ox2 ]·4H2 O (HRh) are synthesized. The compounds are characterized by IR spectroscopy, elemental analysis and single crystal X‐ray diffraction. NaRh‐1, NaRh‐2 and Na2Rh crystallize in space group P 1 . Trans ‐bis(oxalato)diaquarhodic acid exists not only in solution, but can also crystallize as a tetrahydrate (space group C 2/ c ). The formation of various species in solution of rhodium hydroxide in oxalic acid and their redistribution were studied using 103 Rh NMR spectroscopy.